Papel do receptor TRPV1 na nocicepção e no edma induzido por cristais de urato monossódico em ratos - Hoffmeister, Carin Gorete Hendges (2009)
Gout is characterized by the deposition of monosodium urate (MSU) crystals. Despite being one of the most painful forms of arthritis, gout and the mechanisms responsible for its acute attacks are poorly understood. In the present study, we found that MSU caused dose-related nociception (DE50=0.04 (0.01-0.11) mg/paw) and edema (DE50=0.08 (0.04-0.16) mg/paw) when injected into the hind paw of rats. Treatment with the selective TRPV1 receptor antagonist SB366791 largely inhibited nociceptive and edematogenic responses to MSU. Moreover, the desensitization of capsaicin-sensitive afferent fibers as well as the pretreatment with the tachykinin NK1 receptor antagonist RP 67580 also significantly reduced MSU-induced nociception and edema. Once MSU was found to induce mast cell stimulation, we investigated the participation of these cells on MSU effects. Prior degranulation of mast cells by repeat treatment with compound 48/80 decreased MSU-induced nociception and edema or histamine and serotonin levels in the injected tissue. Moreover, pretreatment with the mast cell membrane stabilizer cromolyn effectively inhibited nociceptive and edematogenic responses to MSU. MSU induced a release of histamine, serotonin and tryptase in the injected tissue, confirming mast cell degranulation Furthermore, the antagonism of histaminergic H1 and serotoninergic receptors decreased the edema, but not the nociception, of MSU. Finally, the inhibition of tryptase activity was capable of largely reducing either MSU-induced nociception or edema. Collectively, the present findings demonstrate that MSU produces a nociceptive and edematogenic response mediated by TRPV1 receptor activation and mast cell degranulation.